Prognostic value of quantitative flow ratio in patients with coronary heart disease after percutaneous coronary intervention therapy: a meta-analysis - Chen, Huaigang; Hong, Lang; Xi, Gang; Wang, Hong; Hu, Jing; Liu, Qi; Yang, Liu (Frontiers in Cardiovascular Medicine, 2023)
Background: Coronary atherosclerotic heart disease (CAD) is one of the most serious health and life-threatening diseases. There is no doubt that despite the increasing number of assessment methods used clinically, the prognosis assessment is still not ideal, and newer assessment methods are needed.Objective: To investigate the predictive value of quantitative flow ratio (QFR) for adverse events (VOCE/TLF) in patients after PCI.Method: Eight studies involving 4,173 patients (5,688 vascular lesions) were included.These are studies of the relationship between QFR values and prognosis of adverse cardiac events after PCI. This meta-analysis was performed after quality assessment and data extraction of clinical trials data that met the inclusion criteria.Result: Each of the 8 studies described the cut-off values for the best predictive ability of post-PCI QFR and the hazard ratio (HR) between QFR values and adverse events, respectively. The pooled HR of these studies was 4.72(95%CI:3.29,6.75).Concurrently, lower post-PCI QFR values were associated with the occurrence of individual clinical events (cardiac death/MI/TVR), with RRs of 6.51 (95%CI:4.96, 8.53), 4.83(95%CI:3.08,7.57), and 4.21(95%CI:2.66,6.68), respectively. Conclusion: QFR may have great potential in the assessment of prognosis. It is necessary to measure QFR value after PCI. A lower QFR value after PCI was an important predictor for experiencing adverse events.